2011
DOI: 10.1259/dmfr/24985981
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of accuracy of detection of surface osseous changes in the temporomandibular joint using multidetector computed tomography and cone beam computed tomography

Abstract: CBCT and MDCT accuracy was comparable in detecting surface osseous changes with comparable intraobserver reliabilities. However, since CBCT requires less radiation exposure, it should be encouraged for imaging TMJ with suspected surface osseous changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…14 However, the sensitivities were found to be lower and thus in accordance with Hintze et al 12 The fact that CBCT has a diagnostic accuracy comparable with CT 11,14 was confirmed when assessing condylar fractures in an experimental study on sheep. 15 The sensitivity of CBCT for assessing bone defects is dependent on the size of the defects, as demonstrated by Marques et al 16 and confirmed by Patel et al 17 in their investigations of simulated condylar lesions.…”
Section: Diagnostic Accuracysupporting
confidence: 55%
“…14 However, the sensitivities were found to be lower and thus in accordance with Hintze et al 12 The fact that CBCT has a diagnostic accuracy comparable with CT 11,14 was confirmed when assessing condylar fractures in an experimental study on sheep. 15 The sensitivity of CBCT for assessing bone defects is dependent on the size of the defects, as demonstrated by Marques et al 16 and confirmed by Patel et al 17 in their investigations of simulated condylar lesions.…”
Section: Diagnostic Accuracysupporting
confidence: 55%
“…1 Recent studies have revealed that CBCT is a reliable alternative to multislice CT for the assessment of TMJ space and osseous changes. 2,3 Nowadays, CBCT scanners are available that can give users a choice between high and low spatial resolution settings when scanning a patient. In theory, the higher the number of the spatial resolution used for scanning, the smaller the radiographic details can be observed in the resultant images.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the method employed, the applicability of CBCT in Dentistry appears to be questionable because some studies 19,[22][23][24][25][26] claimed that the CBCT was a reliable and accurate method for verification of changes and carry out measures in TMJ as a whole and specifically in the mandibular condyles. This is especially true when the sagittal and coronal views are considered, being efficient in the determination of changes related to the positioning and shape of the condyle and joint surfaces 27,28 .…”
mentioning
confidence: 99%